ANALISA KEBIJAKAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH PROVINSI JAWA TIMUR DENGAN RPJMD - Bagus Djulig Wijono (DIA: Jurnal Administrasi Publik, 2019)
The ability of the Regional Government in planning the budget is something that is very influential in order to realize the goals set through the Medium Term Development Plan. The change in the paradigm of the government system from centralistic to decentralized (regional autonomy) has the consequence of a change in the development planning paradigm from a sectoral development approach to a regional (regional) approach.This study uses qualitative methods, to see whether the budget planning implemented by the East Java Provincial Government is in accordance with public policy, and sees its potential, taking into account the development of the 2014-2019 Medium Term Development Plan.The results achieved in this study are mostly the budget planning process that is applied in accordance with public policy, which starts from the bottom, although the results obtained are still not fully in accordance with the target. And this is evident that East Java is the province that first applied ebudgeting, so that budget management can be more transparent and accountable.